The impact of gender-role-orientations on subjective career success: A multilevel study of 36 societies - Terpstra-Tong, Jane; Ralston, David A.; Treviño, Len; Karam, Charlotte; Furrer, Olivier; Froese, Fabian; Tjemkes, Brian; Darder, Fidel León; Richards, Malika; Dabic, Marina; Li, Yongjuan; Fu, Pingping; et al. (Journal of vocational behavior, 2022)
We investigate the relationships between gender-role-orientation (i.e., androgynous, masculine, feminine and undifferentiated) and subjective career success among business professionals from 36 societies. Drawing on the resource management perspective, we predict that androgynous individuals will report the highest subjective career success, followed by masculine, feminine, and undifferentiated individuals. We also postulate that meso-organizational culture and macro-societal values will have moderating effects on gender role's impact on subjective career success. The results of our hierarchical linear models support the hypothesized hierarchy of the relationships between gender-role-orientations and subjective career success. However, we found that ethical achievement values at the societal culture level was the only variable that had a positive moderating impact on the relationship between feminine orientation and subjective career success. Thus, our findings of minimal moderation effect suggest that meso- and macro-level environments may not play a significant role in determining an individual's perception of career success. •Gender (biological sex) is not a reliable predictor of subjective career success.•Androgynous gender-role-orientation is associated with the highest subjective career success.•Ethical achievement societal culture raises feminine individuals’ subjective career success.•Organizational and societal cultures have minimal influence on the gender-role-orientations–career-success relationship.